Polyurethane Transparent Dressing Protection on the Insertion Area of Peripheral Intra Venous Catheter (PIVC) - Fathonah, S; Putri, M (KnE Life Sciences, 2019)
One way to prevent infection in PIVC insertion is by dressing. Transparent polyurethane is one type of dressing that is often used in hospitals. Colonization of germs around the PIVC insertion area can cause infection. The objective of this study was to determine the difference in the number of germs in the PIVC insertion area with transparent polyurethane dressings in PKU Muhammadiyah Yogyakarta Hospital and to assess the effectiveness of dressing protection. The design of this study was quasi-experimental with a pretest-posttest design. The samples used are 11 patients and they are collected using purposive sampling. Calculation of the number of germs is carried out using the cup count method. The average number of germs before and after dressing using transparent polyurethane is decreasing in the average amount of 5.09. Analysis of the data using the Wilcoxon test is to determine the difference in the number of germs before and after the dressing. Statistical test results show that changes in the number of germs produced a p value of 0.027 (p value <0.05). The results shows that there is a significant change in the number of germs in PIVC area before and after dressing using transparent polyurethane. The average number of germs after dressing with transparent polyurethane is lower. A subsequent research can be done with a stronger method of Rondomized Control Trial (RCT) with a larger number of samples. Keywords: PIVC insertion area, transparent polyurethane dressing